2017
DOI: 10.1016/j.bmcl.2016.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity relationships of benzylproline-derived inhibitors of the glutamine transporter ASCT2

Abstract: The glutamine transporter ASCT2 has been identified as a promising target to inhibit rapid growth of cancer cells. However, ASCT2 pharmacology is not well established. In this report, we performed a systematic structure activity analysis of a series of substituted benzylproline derivatives. Substitutions on the phenyl ring resulted in compounds with characteristics of ASCT2 inhibitors. Apparent binding affinity increased with increasing hydrophobicity of the side chain. In contrast, interaction of the ASCT2 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 23 publications
(39 reference statements)
11
43
1
Order By: Relevance
“…However, consistent with previous results, ASCT2 does not bind or transport lysine [1,3]. Additionally, we found that apparent affinity increased with decreasing side chain length and L-DAP binding could be inhibited competitively using previously published ASCT2 inhibitors [38]. We propose a mechanism for interaction of ASCT2 with various protonation states of L-DAP ( Figure 1D-G), based on kinetic modeling as well as molecular docking.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, consistent with previous results, ASCT2 does not bind or transport lysine [1,3]. Additionally, we found that apparent affinity increased with decreasing side chain length and L-DAP binding could be inhibited competitively using previously published ASCT2 inhibitors [38]. We propose a mechanism for interaction of ASCT2 with various protonation states of L-DAP ( Figure 1D-G), based on kinetic modeling as well as molecular docking.…”
Section: Introductionsupporting
confidence: 91%
“…To investigate further if the compounds with basic side chains were actually binding to the ASCT2 binding site, we conducted competition experiments at varying concentrations of a competitive inhibitor of ASCT2, (R)-γ-(4-biphenylmethyl)-L-proline (BPP). This compound was previously characterized and competes with alanine for the substrate binding site with a K i of 3 mM [38]. Consistent with the hypothesis of L-DAP acting as a substrate, BPP reduced L-DAP induced inward currents at all concentrations and the results could be fitted with a Michaelis-Menten-like relationship to obtain the apparent binding affinity for L-DAP at three different inhibitor concentrations ( Figure 4A-C).…”
Section: L-dap Competes With Binding Of Substrate and A Competitive Isupporting
confidence: 80%
“…The opening of the HP2 loop increases the accessible surface area, exposing a previously unidentified cryptic pocket which could accommodate a large inhibitor that would be specific to the HP2 open state. In contrast, the closed conformation of HP2 has a small binding site, limiting the size of the inhibitors (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment was done using a library of 29 known ASCT2 ligands, including substrates and inhibitors that were collected from the literature 15,16,24,[46][47][48] and ChEMBL 49 and 1,434 decoys generated with the DUD-E server 50 . Docking was performed with OpenEye FRED 51 as described in our previous work 27 .…”
Section: Asct2 Modeling and Assessmentmentioning
confidence: 99%
“…Because ASCT2 is a pharmacologically important target, multiple small molecule competitive inhibitors have been developed for this protein, using both structure-based rational design and ligand-based approaches (reviewed in reference 22). For example, guided by homology modeling, we discovered and optimized a series of proline-based derivatives as well as other chemical scaffolds that inhibit ASCT2 in low µM potencies 16,23,24 . Notably, these amino acid analog inhibitors, which have large hydrophobic groups in the side chain provided evidence that non-polar interactions within the substrate binding site may be exploited to further increase potency.…”
mentioning
confidence: 99%